30 Years of Gender Inequality and Implications on Curriculum Design in Open and Distance Learning. Issue 1 (11th May 2020) - Koseoglu, Suzan; Ozturk, Tugba; Ucar, Hasan; Karahan, Engin; Bozkurt, Aras
Gender inequality is a pressing issue on a global scale, yet studies on this important issue have stayed on the margins of open and distance learning (ODL) literature. In this study, we critically analyse a batch of ODL literature that is focused on gender inequality in post-secondary and higher education contexts. We use Therborn's social justice framework to inform and guide the study. This is a comprehensive social justice lens that sees inequality as "a life and death issue, " approaching empowerment as a central area of concern. Qualitative content analysis of 30 years of peer-reviewed literature reveals patriarchy and androcentrism as significant mechanisms that continue to produce gender inequality, in particular in women's access to educational resources and formal learning opportunities. We highlight three themes that emerged in the content analysis: (1) ODL and equal opportunity ; (2) Feminism and gender-sensitive curriculum design ; and (3) Culturally relevant curriculum design . We critique views of access to technology-enabled education as an instrument for social justice, and provide a pedagogical model for an ODL curriculum centred on empowerment and agency, two concepts closely linked to existential inequality. We argue that such a curriculum is public service and requires a model of education that is based on participation and co-construction, and lies at the intersection of critical, feminist, and culturally relevant pedagogical practices.